Cyberbullying and Emotional Distress: A Psychological Analysis of Online Behavior - Nuwa, Gisela; Prasetyo, Erwin; Fitri, Mohamad; Wahyuningsih (The Indonesian Institute of Science and Technology Research, 2025)
The rise of digital communication has given birth to a disturbing trend: cyberbullying. Unlike traditional bullying, cyberbullying occurs in a persistent, borderless, and often anonymous online environment, magnifying its psychological impact. This article presents an opinion-based psychological analysis of how cyberbullying contributes to emotional distress, especially among adolescents and young adults. Drawing on key psychological theories such as the General Aggression Model (GAM) and the Stress-Coping Framework, the article explores the complex interplay between online aggression and mental health. A conceptual model is introduced to demonstrate the link between online behavior and emotional consequences. Data from existing literature are synthesized into thematic tables to highlight key trends and coping strategies. The findings emphasize the urgent need for proactive psychological interventions, digital literacy education, and supportive online communities.